23Na Magnetic Resonance Imaging of the Lower Leg of Acute Heart Failure Patients during Diuretic Treatment - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Garlichs, Christoph; Janka, Rolf Matthias; Luft, Friedrich C.; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (PLoS ONE, 2015)
Na+ can be stored in muscle and skin without commensurate water accumulation. The aim of this study was to assess Na+ and H2O in muscle and skin with MRI in acute heart failure patients before and after diuretic treatment and in a healthy cohort.Nine patients (mean age 78 years; range 58-87) and nine age and gender-matched controls were studied. They underwent 23Na/1H-MRI at the calf with a custom-made knee coil. Patients were studied before and after diuretic therapy. 23Na-MRI gray-scale measurements of Na+-phantoms served to quantify Na+-concentrations. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na+-levels did not change during therapy. Mean Na+-concentrations in muscle and skin decreased after furosemide therapy (before therapy: 30.7±6.4 and 43.5±14.5 mmol/L; after therapy: 24.2±6.1 and 32.2±12.0 mmol/L; p?0.05 and p?0.01). Water content measurements did not differ significantly before and after furosemide therapy in muscle (p = 0.17) and only tended to be reduced in skin (p = 0.06). Na+-concentrations in calf muscle and skin of patients before and after diuretic therapy were significantly higher than in healthy subjects (18.3±2.5 and 21.1±2.3 mmol/L).23Na-MRI shows accumulation of Na+ in muscle and skin in patients with acute heart failure. Diuretic treatment can mobilize this Na+-deposition; however, contrary to expectations, water and Na+-mobilization are poorly correlated.
EVALuna2:3828

Anti-inflammatory effects of Danshen on human vascular endothelial cells in culture - Stumpf, Christian; Fan, Quiaoling; Hintermann, Christian; Raaz-Schrauder, Dorette; Kurfuerst, Ingrid; Losert, Sigrid; Pflederer, Wolfgang; Achenbach, Stephan; Daniel, Werner; Garlichs, Christoph (American Journal of Chinese Medicine, 2013)
Inflammation plays a crucial role in the pathophysiology of atherosclerosis. Besides cytokines, chemokines and cell adhesion molecules, CD40 and P-selectin play important roles as key regulators of the inflammatory process in atherosclerosis. Danshen (DS) is commonly used in traditional Chinese medicine for therapy of cardiovascular diseases such as coronary artery disease. The aim of the present study was to evaluate the protective effects of DS with respect to possible anti-inflammatory effects. Human umbilical vein endothelial cells as well as platelets were incubated with an extract of DS or one of its major ingredients salvianolic acid B (Sal B), tanshinone IIA (Tansh) and protocatechuic acid (Protoc) under tumor necrosis factor (TNF)-α or ADP stimulation. Expression of CD40 and cellular adhesion molecules (VCAM-1/ICAM-1) were assessed via flow cytometry. Levels of interleukin (IL)-6, IL-8, monocyte-chemoattractant-protein (MCP)-1 as well as soluble VCAM1 and ICAM-1 in the supernatants were examined via luminex based analysis. Treatment with DS attenuated TNF-α induced expression of CD40. Furthermore, the expression of VCAM-1 and ICAM-1 as well as the release of soluble VCAM-1 and ICAM-1 were downregulated. In the cell supernatants we also observed a significant reduction of IL-6, IL8 and MCP-1. DS and its major ingredients, Sal B and Protoc, significantly inhibited TNF-induced expression and release of adhesion molecules, cytokines and chemokines as well as ADP-induced expression of platelet P-selectin. Because of the key roles of inflammatory mediators in the etiology of atherosclerosis, this work provides useful insight in understanding the pharmacological efficacy of Chinese herbal medicine. © 2013 World Scientific Publishing Company Institute for Advanced Research in Asian Science and Medicine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adhesion Molecules; Cytokines; Danshen; Endothelial Cells

Association of systemic inflammation markers with the presence and extent of coronary artery calcification - Raaz-Schrauder, Dorette; Klinghammer, Lutz; Baum, Christina; Frank, Thomas; Lewczuk, Piotr; Achenbach, Stephan; Cicha, Iwona; Stumpf, Christian; Wiltfang, Jens; Kornhuber, Johannes; Daniel, Werner; Garlichs, Christoph (Cytokine, 2012)
Background: Coronary artery calcification (CAC) is a marker for the presence and extent of coronary atherosclerotic plaques and can be detected non-invasively by multi-detector row CT (MDCT). Well known predictors of CAC are age, gender, and the classical atherogenic risk factors. CAC is associated with atherosclerotic plaque burden, but it is still elusive if atherosclerosis-relevant cytokines and chemokines are also associated with CAC. Methods: We conducted a clinical study among 455 consecutive individuals who underwent coronary calcium assessment performed by MDCT. Before MDCT, blood was drawn and subsequently analyzed for 20 different atherosclerosis-relevant cytokines and chemokines using a Luminex-laser-based fluorescence analysis. Results: Using univariate analyses, CAC patients revealed significantly higher levels of the chemokines IP-10 (P=0.047) and eotaxin (P=0.031) as compared to non-CAC patients. In multivariate analyses using common thresholds for calcium burden, the three cytokines interleukin-6 (P=0.028), interleukin-8 (P=0.009), and interleukin-13 (P=0.024) were associated with high coronary calcium levels after adjustment for classical variables and risk factors. Conclusions: In a large group of individuals with atypical chest pain and a low to intermediate likelihood for coronary artery disease elevated plasma levels of IL-6 and reduced levels of IL-8 and IL-13 were predictive for distinct coronary artery calcification. These findings support a specific role of these cytokines in coronary calcification. © 2011 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Atherosclerosis; Cardiac computed tomography; Coronary calcification; Cytokines; Inflammation

Atorvastatin enhances interleukin-10 levels and improves cardiac function in rats after acute myocardial infarction - Stumpf, Christian; Petzi, Stephan; Seybold, Katrin; Wasmeier, Gerald; Arnold, Martin; Raaz, Dorette; Yilmaz, Atilla; Daniel, Werner; Garlichs, Christoph (Clinical Science, 2009)
LV (left ventricular) remodelling is the basic mechanism of HF (heart failure) following MI (myocardial infarction). Although there is evidence that pro-inflammatory cytokines [including TNF-α (tumour necrosis factor-α) and IL-6 (interleukin-6)] are involved in the remodelling process, only little is known about the role of anti-inflammatory cytokines, such as IL-10. As accumulating evidence has revealed that statins possess anti-inflammatory properties, the aim of the present study was to elucidate the effect of atorvastatin on the modulation of the anti-inflammatory cytokine IL-10 and its effect on LV function in rats with HF subsequent to MI. Rats with MI, induced by permanent LAD (left anterior descending) branch coronary artery ligation, were treated for 4 weeks with atorvastatin (10 mg · kg-1 of body weight · day-1 via oral gavage) starting on the first day after induction of MI. Cardiac function was assessed by echocardiography and cardiac catheterization 4 weeks after MI induction. Membrane-bound and soluble fractions of TNF-α, IL-6 and IL-10 protein, the TNF-α/IL-10 ratio, serum levels of MCP-1 (monocyte chemoattractant protein-1) as well as myocardial macrophage infiltration were analysed. Treatment with atorvastatin significantly improved post-MI LV function (fractional shortening, + 120 %; dP/dtmax, + 147 %; and LV end-diastolic pressure, - 27 %). Furthermore atorvastatin treatment markedly decreased the levels of TNF-α, IL-6 and MCP-1, reduced myocardial infiltration of macrophages and significantly increased myocardial and serum levels of the anti-inflammatory cytokine IL-10. Thus the balance between pro-inflammatory and anti-inflammatory cytokines was shifted in the anti-inflammatory direction, as shown by a significantly decreased TNF-α/IL-10 ratio. Atorvastatin ameliorated early LV remodelling and improved LV function in rats with HF subsequent to MI. Our study suggests that the modulation of the balance between pro- and anti-inflammatory cytokines towards the anti-inflammatory cytokine IL-10 is one salutary mechanism underlying how atorvastatin influences post-MI remodelling and thus improves LV function. © The Authors Journal compilation © 2009 Biochemical Society.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Atorvastatin; Heart failure; Inflammation; Interleukin-10; Myocardial infarction

CD40/CD154 system and pro-inflammatory cytokines in young healthy male smokers without additional risk factors for atherosclerosis - Garlichs, Christoph; Cicha, Iwona; Raaz-Schrauder, Dorette; Meyer, L.; Stumpf, Christian; Klinghammer, Lutz; Yilmaz, Atilla; Daniel, Werner (Inflammation Research, 2009)
Objective and design:: Atherosclerosis, as an inflammatory disease, is characterized by pathologically altered levels of cytokines. We investigated whether smoking affects the CD40/CD154 system and pro-inflammatory cytokines in young males without other risk factors for atherosclerosis. Subjects:: Young male smokers (n=13) and 14 non-smoking controls were investigated. Methods:: The differences in CD40/CD154 system and serum cytokines between the groups were measured using flow cytometry and ELISA. Results:: In smokers, there was a strong trend (P<0.06) for increased CD40 expression on platelets as compared with non-smokers. However, there were no significant differences in CD40 expression on monocytes or in CD154 expression on platelets and T-cells between smokers and non-smokers. There was a strong trend for increased platelet-monocyte aggregates in smokers (P<0.06). Also, smokers had slightly but not significantly elevated hsCRP and IL-6 levels, and slightly decreased TNF-α and MCP-1. Interestingly, IL-18, a cytokine which has the ability to promote both Th1 and Th2 responses, was significantly decreased in smokers group (P=0.03 vs controls). Conclusions:: In young healthy males, smoking is not associated with dramatic changes in CD40/CD154 system. However, cigarette smoke alters the secreted cytokine profile, leading to significant decrease in systemic IL-18 levels. © 2009 Birkhäuser Verlag, Basel.
CRIS-Team Scopus Importer:2023-07-10
Keywords: CD40/CD154; Cytokines; Interleukin-18; Platelets; Smoking

Decreased numbers of regulatory T cells are associated with human atherosclerotic lesion vulnerability and inversely correlate with infiltrated mature dendritic cells - Dietel, Barbara; Cicha, Iwona; Voskens, Caroline; Verhoeven, Eric; Achenbach, Stephan; Garlichs, Christoph (Atherosclerosis, 2013)
Purpose: Mature dendritic cells (DCs) play a crucial role in the inflammatory process within atherosclerotic lesions by stimulation of effector T cells, which can contribute to plaque instability. Interactions between DCs and regulatory T cells (Treg), which regulate immune response by attenuating acute inflammation, are postulated to be involved in the pathogenesis of autoimmune diseases. We investigated a possible correlation between infiltrated DCs and Treg in human atherosclerotic plaques. Methods: Cross-sections of 40 human carotid endarterectomy specimens were classified into groups of stable and vulnerable plaques using Trichrome staining. Immunohistochemical staining of plaques was used to detect infiltrated total (S100) and mature DCs (fascin, DC-LAMP, CD83), Treg (CD3, Foxp3), and to analyze the inflammatory state of the plaques (CD3, COX-2, CD68). In addition, RNA was isolated from plaque specimens and quantitative real-time PCR was performed to analyze transcription rates of DC markers (CD11c, CD209, HLA-DR), maturation markers (CD80, CD83, CD86), Treg-associated genes (CTLA-4, Foxp3) and of pro- and anti-inflammatory cytokines (TGFβ-family, IL-10, IFN-γ, IL-17α, IL-6). Migration assays and adhesion experiments were performed, to investigate the effects of Treg on mature DCs invitro. Results: As compared with stable plaques, vulnerable lesions were characterized by increased numbers of COX-2-expressing cells and T lymphocytes, indicating an enhanced inflammatory process. In vulnerable plaques, numbers of total and mature DCs were significantly higher in the inflammatory plaque shoulder, whereas the numbers of Treg were decreased compared to stable plaques. This inverse correlation and the association of the observed infiltration rates with plaque stability, were confirmed by PCR analyses, showing increased transcription levels of DC-specific markers, decreased mRNA expression of Treg-associated genes and decreased anti-inflammatory cytokines in vulnerable atherosclerotic plaques. In vitro, pre-incubation of mature DCs with Treg resulted in decreased DC migration and inhibited the adhesion of DCs to endothelial cells under non-uniform shear stress. Conclusions: The results of our study provide novel insights in the direct interaction of mature DCs and Treg in plaque inflammation and stability. © 2013 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Carotid plaques; Dendritic cells; Immunologic tolerance; Regulatory T cells

Differentiated antiplatelet therapy for acute coronary syndromes - Schaefer, A.; Arntz, H. R.; Boudriot, E.; Garlichs, Christoph; Hoffmann, S.; Ince, H.; Klingenheben, T.; Weil, J.; Zugck, C.; Helms, T. M.; Silber, S. (Deutsche Medizinische Wochenschrift, 2014)
Dual antiplatelet therapy is the cornerstone of maintenance medication following invasive treatment of patients with acute coronary syndromes (ST elevation myocardial infarction, non-ST elevation myocardial infarction, unstable angina). Over the last decade, P2Y12 inhibition in addition to low-dose acetylsalicylic acid has been intensively debated. The debate was enriched by the results of the large phase III clinical trials for prasugrel (TRITON) and ticagrelor (PLATO) compared to clopidogrel in patients with acute coronary syndromes. This article summarizes the critical details und subanalyses of both study programmes and highlights on clinical decision making when using the three P2Y12 blockers in acute coronary syndromes. A special focus is on higher risk patients such as those with ST elevation myocardial infarction and those with coexisting diabetes, but also on minimizing relevant bleedings, which are common during more intense platelet inhibition.
EVALuna2:11996

Different treatment settings of Granulocyte-Colony Stimulating Factor and their impact on T cell-specific immune response in experimental stroke - Dietel, Barbara; Cicha, Iwona; Achenbach, Stephan; Kollmar, Rainer; Garlichs, Christoph; Tauchi, Miyuki (Immunology Letters, 2014)
Cerebral ischemia is associated with infectious complications due to immunosuppression and decreased T lymphocyte activity. G-CSF, which has neuroprotective properties, is known to modulate inflammatory processes after induced stroke. The aim of our study was to investigate the impact of G-CSF in experimental stroke and to compare two different modes of treatment, focusing on circulating T lymphocytes.Cerebral ischemia was induced in Wistar rats by occlusion of the middle cerebral artery, followed by reperfusion after 1h. G-CSF was applied either as a single dose 30 min after occlusion, or daily for seven days. Silver staining was used to determine infarct size. T lymphocytes in the peripheral blood were measured before and 7 days after induced cerebral ischemia by flow cytometry. In addition, migration of CD3-expressing T lymphocytes into the brain was investigated by immunohistochemistry.Both single dose and daily treatment with G-CSF significantly reduced infarct size. A significant improvement of neurological outcome was only observed after single application of G-CSF. While a decrease in peripheral T lymphocytes was detected seven days after induced stroke, no reduction was observed in the G-CSF-treated groups. Apart from that, G-CSF significantly reduced the number of brain migrated T lymphocytes in both treatment settings as compared to vehicle.A single dose of G-CSF exerted neuroprotective effects in ischemic stroke, which were less pronounced after daily G-CSF application. Both treatment strategies inhibited stroke-induced reduction of T lymphocytes in peripheral blood, which may have contributed to the reduction of infarct size.
EVALuna2:12004

Elevated VEGF-plasma levels in young patients with mild essential hypertension - Stumpf, Christian; Jukic, Jelena; Yilmaz, A.; Raaz, Dorette; Schmieder, Roland; Daniel, Werner; Garlichs, Christoph (European Journal of Clinical Investigation, 2009)
Background: Growing evidence shows that inflammation plays a pivotal role in the pathophysiology of essential hypertension (EH). Vascular endothelial cell growth factor (VEGF) is currently discussed as a possible mediator of inflammation. To investigate the hypothesis that VEGF plays a role as an inflammatory mediator in EH we performed the present pilot study of young patients in a very early stage of EH. Materials and methods: 15 young patients with mild EH [33.8 ± 7.3 years, systolic blood pressure (SBP): 143.8 ± 10.5 mmHg, diastolic blood pressure (DBP): 88.2 ± 11.1 mmHg, mean arterial pressure (MAP) 106.6 ± 10.4 mmHg] and 15 healthy controls (31.7 ± 10.6 years) were examined. Blood was drawn from a peripheral vein and serum levels of VEGF, monocyte-chemoattractant-protein (MCP)-1, high-sensitivity C-reactive protein (hsCRP), interleukin (IL)-6, and tumour-necrosis-factor (TNF)-α were measured via commercially available enzyme-linked immunoassays. Results: Hypertensives showed increased plasma levels of VEGF (P < 0.05) and MCP-1 (P < 0.05). VEGF positively correlated with MAP (r = 0.46, P < 0.05) and MCP-1 (r = 0.63, P < 0.01). Multivariate analysis demonstrated VEGF to be an independent predictor of MCP-1 levels. Furthermore, hypertensives had higher levels of hsCRP (P < 0.01), IL-6 (P < 0.001) and TNF-α (P < 0.05). IL-6 levels correlated with SBP (r = 0.59, P < 0.001), DBP (r = 0.67, P < 0.001) and MAP (r = 0.46, P < 0.001). A significant positive correlation was also found between hsCRP levels and SBP (r = 0.39, P < 0.05). Conclusions: This pilot study demonstrates that in an early state of EH, inflammatory pathways have already been activated. Besides classical pro-inflammatory cytokines, VEGF serum levels are significantly elevated. The positive correlation of VEGF with MCP-1 is suggestive for the already described induction of MCP-1 via VEGF. © 2008 The Authors.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Cytokines; Hypertension; Inflammation; VEGF

Emergence of dendritic cells in the myocardium after acute myocardial infarction - implications for inflammatory myocardial damage - Yilmaz, Atilla; Dietel, Barbara; Cicha, Iwona; Schubert, Katja; Hausmann, Roland; Daniel, Werner; Garlichs, Christoph; Stumpf, Christian (International Journal of Biomedical Science, 2010)
Dendritic cells (DC) are crucial for T cell mediated immune responses. Recently, we observed a significant decrease in circulating myeloid DC precursors in patients with acute myocardial infarction (AMI). The aim of the present study was to investigate whether myeloid DC are present in infarcted myocardium. Myocardial specimens of 10 patients with AMI and 7 accident victims (controls) were collected after autopsy. In immunostainings the presence of DC (CD209+, fascin+), T cells (CD3+), macrophages (CD68+), and HLA-DR expression was analyzed. Significantly higher numbers of CD209+-DC (97 vs. 44 cells/0.25 mm2, p=0.03), fascin+-DC (54 vs. 8 cells/0.25 mm2, p=0.02), T cells (27 vs. 6 cells/0.25 mm2, p=0.02), and macrophages (44 vs. 6 cells/0.25 mm2, p=0.01) associated with high HLA-DR expression were detected in infarcted myocardium. Frequent colocalizations of DC and T cells were observed. In occluded coronary arteries numerous DC, T cells, macrophages and high HLA-DR expression were found. We show that DC are present in infarcted myocardium after AMI. High HLA-DR expression and the colocalization with T cells suggest that they might trigger an immune response leading to further myocardial damage.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Adaptive immunity; Atherosclerosis; Dendritic cells; Innate immunity; Leukocyte

FcγRIIa genotype is associated with acute coronary syndromes as first manifestation of coronary artery disease - Raaz, Dorette; Herrmann, Martin; Ekici, Arif Bülent; Klinghammer, Lutz; Lausen, Berthold; Voll, Reinhard E.; Leusen, Jeanette H.W.; van de Winkel, Jan G.J.; Daniel, Werner; Reis, André; Garlichs, Christoph (Atherosclerosis, 2009)
Objective: Identification of clinically relevant determinants for acute coronary syndromes (ACS) promises reduction of ACS-associated mortality. C-reactive protein (CRP) has proved to be useful identifying people at risk for cardiovascular events. However, it is unknown whether genetic variants at Fcγ receptor IIa (FcγRIIa), the main receptor for CRP, are involved in CRP-related cardiovascular risk. We evaluated the potential impact of FcγRIIa through a genetic association study in patients with ACS. Methods and results: We conducted a genetic association study among 701 consecutive patients with first event of ACS compared to 467 patients with stable angina pectoris. All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa, where the arginine (R) allele results in an increased signal transduction upon CRP binding. In our study, the R/R131 genotype was significantly associated with ACS as the first manifestation of coronary artery disease (P = 1.2 × 10-9, odds ratio 2.86, 95% CI: 2.06-3.99) compared to the non-R/R131 genotype. Conclusions: Our data show a genetic association of the FcγRIIa R/R131 genotype with a more frequent occurrence of ACS as the first manifestation of coronary artery disease, probably mediated via its interaction with CRP. Genotyping of this FcγRIIa variant could help to improve risk stratification in the course of coronary disease in the future. © 2009 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Acute coronary syndrome; Fcγ receptor IIa; Gene polymorphism; Inflammation

Impact of telmisartan on the inflammatory state in patients with coronary atherosclerosis - Influence on IP-10, TNF-α and MCP-1 - Klinghammer, Lutz; Urschel, Katharina; Cicha, Iwona; Lewczuk, Piotr; Raaz-Schrauder, Dorette; Achenbach, Stephan; Garlichs, Christoph (Cytokine, 2013)
Background: Hypertension is one of the most prominent risk factors for coronary artery disease (CAD). Treatment of hypertension is therefore important for reducing cardiovascular events and the progression of atherosclerosis. Several treatment strategies are common in clinical practice for example the use of ACE-blockers or angiotensin receptor II blockers (ARBs), so called sartans. Telmisartan, belonging to the class of ARBs, was shown to exert anti-inflammatory effects besides the blood pressure lowering. Methods: In this work, two separate substudy groups of hypertensives were compared. 16 patients with arterial hypertension have been treated with telmisartan (initial 40. mg Kinzalmono®) for 7.3±4.4 months. The telmisartan group was compared to a matched control group including 31 hypertensive patients without telmisartan treatment with a follow up period of 1.9±0.5 years. Serum samples from the beginning and the end of follow up were analyzed with Luminex® technology for 26 cytokines and chemokines. The baseline scores of coronary artery calcification (CAC) were gathered by multislice detector computer tomography. Results: After 7. months of telmisartan treatment and 2. years in control patients most of the measured analytes did not change significantly. MCP-1 (P=0.001; P<0.001) was increased significantly in both telmisartan and control group. The relative decrease in IP-10 and TNF-α levels was observed in telmisartan group, as opposed to the increase in control (telmisartan vs. control P=0.048; P=0.01). No linear rank-correlation between measured analytes and the initial CAC was found. Conclusion: Telmisartan reduced blood pressure in patients with atherosclerosis and arterial hypertension within a short time period, whereas the inflammatory status of these patients remained largely unchanged. An involvement of telmisartan in the regulation of inflammatory and anti-inflammatory mediators in the context of CAD and CAC is possible, but cannot clearly be assumed based on the present findings. © 2013.
CRIS-Team Scopus Importer:2023-03-08
Keywords: %Δa; Δ; Δa; Atherosclerosis; CAC; Chemokines; Cytokines; Risk factors; Telmisartan

MCS-18, a natural product isolated from Helleborus purpurascens, inhibits maturation of dendritic cells in ApoE-deficient mice and prevents early atherosclerosis progression - Dietel, Barbara; Muench, Rabea; Kühn, Constanze; Kerek, Franz; Steinkasserer, Alexander; Achenbach, Stephan; Garlichs, Christoph; Zinser, Elisabeth (Atherosclerosis, 2014)
Inflammation accelerates both plaque progression and instability in the pathogenesis of atherosclerosis. The inhibition of dendritic cell (DC) maturation is a promising approach to suppress excessive inflammatory immune responses and has been shown to be protective in several autoimmune models. The aim of this study was to investigate the immune modulatory effects of the natural substance MCS-18, an inhibitor of DC maturation, regarding the progression of atherosclerosis in ApoE-deficient mice.ApoE-deficient mice were fed for twelve weeks with a Western-type diet (n = 32) or normal chow (control group; n = 16). Animals receiving high-fat diet were treated with MCS-18 (500 ?g/kg body weight, n = 16) or saline (n = 16) twice a week. After 12 weeks, animals were transcardially perfused and sacrificed. The percentage of mature DCs (CD3(-)/CD19(-)/CD14(-)/NK1.1(-)/CD11c(+)/MHCII(+)/CD83(+)/CD86(+)) and T cell subpopulations (CD4(+)/CD25(+)/Foxp3(+), CD3/CD4/CD8) was analyzed in peripheral blood and in the spleen using flow cytometry. Plaque size was determined in the aortic root and the thoracoabdominal aorta using en-face staining. Immunohistochemical stainings served to detect inflammatory cells in the aortic root. Several cytokines and chemokines were determined in serum using multiplex assays.In splenic cells derived from saline-treated atherosclerotic mice an increased DC maturation, reflected by the upregulation of CD83 and CD86 expression, was observed. The enhanced expression of both maturation markers was absent in MCS-18 treated atherosclerotic mice. While the percentage of splenic Foxp3 expressing Treg was increased in animals receiving MCS-18 compared to saline-treated atherosclerotic mice, cytotoxic T cells were reduced in the spleen and in atherosclerotic lesions of the aortic root. Furthermore, proatherogenic cytokines (e.g. IL-6 and IFN-?) and chemokines (e.g. MIP-1?) were decreased in serum of MCS-18-treated animals when compared to saline-treated atherosclerotic mice. Also plaque size in the aortic root and the thoracoabdominal aorta was significantly lower following administration of MCS-18.This study provides for the first time evidence that MCS-18 is able to prevent the onset of atherosclerosis in ApoE-deficient mice. The observed anti-atherogenic effect is associated with the suppression of DC maturation and an inhibited migration and proliferation of cytotoxic T cells.
EVALuna2:11981

Nanomedicine in diagnostics and therapy of cardiovascular diseases: Beyond atherosclerotic plaque imaging - Cicha, Iwona; Lyer, Stefan; Alexiou, Christoph; Garlichs, Christoph (Nanotechnology Reviews, 2013)
Atherosclerosis results from the accumulation of the modified lipoproteins within the artery walls, which triggers complex vascular inflammatory processes. Although the pharmacologic agents for the treatment of clinical manifestations of atherosclerosis are available, their systemic delivery has serious disadvantages, such as considerable side effects or low efficacy at tolerated doses. Moreover, the treatment of atherosclerosis using the interventional techniques bears further shortcomings: the implanted stents require a lengthy antiplatelet therapy and carry the risk of in-stent restenosis. In the surgical approach to atherosclerosis, apart from the overall risk of open heart surgery, the lack of adequate venous material for bypasses constitutes a common problem. The nanotechnology has the potential to overcome the disadvantages of the current therapy of atherosclerosis, e.g., by the formation of nanosized assemblies for the earlier detection of atherosclerotic lesions and for cell-specific delivery of therapeutics. Replacing the current systemic pharmacological approach by a locally targeted treatment of plaques can substantially minimize the adverse effects, by lowering the drug cytotoxicity and reducing the required dosage. Moreover, a new generation of nanotechnological approaches to the revascularization procedures is now emerging, e.g., vascular tissue engineering utilizing the magnetic nanoparticles or the design of stents with the reduced risk of thrombosis and restenosis. This review discusses the possible applications of the nanomedical approaches in the treatment of cardiovascular diseases.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Atherosclerosis; Nanoparticles; Plaque imaging; Stent design; Vascular tissue engineering

Patients with atypical chest pain show associations with pro-atherogenic cytokines and levels of sRANKL and OPG - Raaz-Schrauder, D.; Stumpf, Christian; Schrauder, Michael G.; Lewczuk, Piotr; Dietel, B.; Garlichs, Christoph; Achenbach, Stephan; Klinghammer, Lutz (2016)
EVALuna2:33388

Patients with unstable angina pectoris show an increased frequency of the Fc gamma RIIa R131 allele - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Munoz, Luis Enrique; Klinghammer, Lutz; Voll, Reinhard E.; Leusen, Jeanette H.W.; Van De Winkel, Jan G.J.; Reis, André; Schett, Georg; Garlichs, Christoph; Herrmann, Martin (Autoimmunity, 2012)
Patients with Systemic Lupus Erythematosus (SLE) carry an increased risk for the development of coronary artery disease (CAD). The R131 allele of the Fc gamma receptor IIa (FcγRIIa) is associated with SLE incidence and disease severity but also with CAD. Compared to stable angina pectoris (SAP) the unstable angina (UAP), as a manifestation of destabilizing CAD, is associated with increased risk of persistent instability, myocardial infarction, and death. Identification of clinically relevant determinants for unstable angina promises reduction of UAP-associated mortality in patients with SLE. We conducted a clinical study among 553 consecutive patients with stable angina pectoris (n 330) and unstable angina pectoris (n 223). All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa. UAP, but not SAP was significantly associated with the R/R131 genotype (P < 0.001). In troponin-negative patients with angina carrying the R/R131 genotype the odds ratio for suffering from UAP was 4.02 (95% confidence interval, 2.526.41) compared to those with non-R/R131 genotypes. In a multivariable analysis, the R/R131 genotype independently predicted the risk for development of UAP in a model adjusted for classical atherogenic risk factors. Our data imply that risk stratification of SLE- and other high risk patients with troponin-negative angina could be significantly improved by FcγRIIa genotyping. © Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Allele R131; Coronary disease; Fc gamma receptor IIa; SLE; Stable; Unstable angina pectoris

Predictive value of the decrease in circulating dendritic cell precursors in stable coronary artery disease - Yilmaz, Atilla; Schaller, Tina; Cicha, Iwona; Altendorf, Regina; Stumpf, Christian; Klinghammer, Lutz; Ludwig, Josef; Daniel, Werner; Garlichs, Christoph (Clinical Science, 2009)
DCs (dendritic cells) are present in atherosclerotic lesions leading to vascular inflammation, and the number of vascular DCs increases during atherosclerosis. Previously, we have shown that the levels of circulating DCPs (DC precursors) are reduced in acute coronary syndromes through vascular recruitment. In the present study, we have investigated whether DCP levels are also reduced in stable CAD (coronary artery disease). The levels of circulating mDCPs (myeloid DCPs), pDCPs (plasmacytoid DCPs) and tDCP (total DCPs) were investigated using flow cytometry in 290 patients with suspected stable CAD. A coronary angiogram was used to evaluate a CAD score for each patient as follows: (i) CAD excluded (n = 57); (ii) early CAD (n = 63); (iii) moderate CAD (n = 85); and (iv) advanced CAD (n = 85). Compared with controls, patients with advanced stable CAD had lower HDL (high-density lipoprotein)-cholesterol (P = 0.03) and higher creatinine (P = 0.003). In advanced CAD, a significant decrease in circulating mDCPs, pDCPs and tDCPs was observed (each P < 0.001). A significant inverse correlation was observed between the CAD score and mDCPs, pDCPs or tDCPs (each P < 0.001). Patients who required percutaneous coronary intervention or coronary artery bypass grafting had less circulating mDCPs, pDCPs and tDCPs than controls (each P < 0.001). Multiple stepwise logistic regression analysis suggested mDCPs, pDCPs and tDCPs as independent predictors of CAD. In conclusion, we have shown that patients with stable CAD have significantly lower levels of circulating DCPs than healthy individuals. Their decrease appears to be an independent predictor of the presence of, and subsequent therapeutic procedure in, stable CAD. © The Authors Journal compilation © 2009 Biochemical Society.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Atherosclerosis; Coronary artery disease; Dendritic cell; Immune system; Inflammation

Rubbing salt into wounded endothelium: sodium potentiates proatherogenic effects of TNF-? under non-uniform shear stress - Wild, Johannes; Soehnlein, Oliver; Dietel, Barbara; Urschel, Katharina; Garlichs, Christoph; Cicha, Iwona (Thrombosis and Haemostasis, 2014)
Increased consumption of sodium is a risk factor for hypertension and cardiovascular diseases. In vivo studies indicated that high dietary sodium may have a direct negative influence on endothelium. We investigated the effects of high sodium on the endothelial activation during early steps of atherogenesis. Endothelial cells (HUVECs) grown in a model of arterial bifurcations were exposed to shear stress in the presence of normal or high (+ 30 mmol/l) sodium. Adherent THP-1 cells, and the adhesion molecule expression were quantified. Sodium channel blockers, pathways' inhibitors, and siRNA against tonicity-responsive enhancer binding protein (TonEBP) were used to identify the mechanisms of sodium effects on endothelium. ApoE-deficient mice on low-fat diet received water containing normal or high salt (8% w/v) for four weeks, and the influence of dietary salt on inflammatory cell adhesion in the common carotid artery and carotid bifurcation was measured by intravital microscopy. In vitro, high sodium dramatically increased the endothelial responsiveness to tumour necrosis factor-? under non-uniform shear stress. Sodium-induced increase in monocytic cell adhesion was mediated by reactive oxygen species and the endothelial nitric oxygen synthase, and was sensitive to the knockdown of TonEBP. The results were subsequently confirmed in the ApoE-deficient mice. As compared with normal-salt group, high-salt intake significantly enhanced the adhesion of circulating CD11b+ cells to carotid bifurcations, but not to the straight segment of common carotid artery. In conclusion, elevated sodium has a direct effect on endothelial activation under atherogenic shear stress in vitro and in vivo, and promotes the endothelial-leukocyte interactions even in the absence of increased lipid concentrations.
EVALuna2:12000

Serum levels of the Th1 chemoattractant interferon-gamma-inducible protein (IP) 10 are elevated in patients with essential hypertension - Stumpf, Christian; Auer, Claudia; Yilmaz, Atilla; Lewczuk, Piotr; Klinghammer, Lutz; Schneider, Markus; Daniel, Werner; Schmieder, Roland; Garlichs, Christoph (Hypertension Research, 2011)
Growing evidence shows that inflammation has a pivotal role in the pathophysiology of essential hypertension (EH). Although it has been acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages, but T lymphocytes have recently become the center of interest. The goal of our study was to evaluate the role of T-cell-specific cytokines in the pathogenesis of EH. The study examined 39 patients with EH (57.7±6.8 years, systolic blood pressure (SBP) 157.5±11.8 mm Hg, diastolic blood pressure 92.2±12.9 mm Hg, mean arterial pressure 113.9±12.6 mm Hg) and 30 healthy, normotensive controls (55.2±4.9 years). Blood was drawn from a peripheral vein, and serum levels of interferon-inducible protein (IP)-10 and interleukins (IL)-4,-7 and-13 were measured by a multiplexing assay. Hypertensive patients had significantly higher levels of IP-10, IL-4, IL-7 and IL-13 than control subjects. When the patients were classified into tertiles according to their serum IP-10 levels (T1: 41.2-9±4.1 pg ml-1; T2: 103.4-1±62.5 pg ml 1; T3: 171.7-443.5 pgml 1), the patients classified into the highest tertile also had the highest blood pressure. In a correlation analysis, plasma IP-10 concentration was significantly associated with SBP (r0.59, P<0.001). Furthermore, hypertensives with microalbuminuria, an early sign of hypertensive target organ damage, had the highest IP-10 levels. A stepwise multivariate regression analysis revealed IP-10 as the strongest independent predictor of SBP (P<0.01). In conclusion, our study provides new insights into the pathophysiological mechanisms in EH linking inflammation and IP-10. However, these preliminary results need to be confirmed in larger trials. © 2011 The Japanese Society of Hypertension All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: cytokines; inflammation; IP-10; microalbuminuria; T-cells

Soft–matrices based on Fibrous Proteins for Biofabrication - Silva Lourenco, Rauqel; Sarker, Bapi; Singh, Raminder; Cicha, Iwona; Roether, Judith; Kaschta, Joachim; Detsch, Rainer; Garlichs, Christoph; Schubert, Dirk W.; Boccaccini, Aldo R. (14th BIONANO-MATERIALS, 2013)

The proinflammatory effect of C-reactive protein on human endothelial cells depends on the Fc?RIIa genotype - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Klinghammer, Lutz; Stumpf, Christian; Achenbach, Stephan; Herrmann, Martin; Reis, André; Garlichs, Christoph (Thrombosis Research, 2014)
The stimulatory effects of CRP (C-reactive protein) on endothelial cells are mainly mediated via Fc?RIIa. This receptor exists in two different allotypes bearing either arginine (R131) or histidine (H131) at the extracellular amino acid position 131 of the mature protein, but only Fc?RIIa-R131 displays high avidity for CRP. This study investigated the role of the Fc?RIIa genotype in CRP-stimulated endothelial cells.We tested the effects of CRP on expression of the adhesion molecules ICAM-1, VCAM-1, and E-selectin, as well as the endothelial release of pro-inflammatory molecules as a function of the Fc?RIIa-genotype (Fc?RIIa-H/H131, Fc?RIIa-H/R131, Fc?RIIa-R/R131) in HUVEC (Human Umbilical Vein Endothelial Cells). HUVEC were grouped according to their Fc?RIIa status by genotyping with an allele specific nested-PCR. The expression of ICAM-1, VCAM-1, and E-selectin on HUVEC was detected by flow cytometry. The release of soluble markers (sCD40L, IL-6, IL-8, MCP-1, tPA, sP-selectin, and sVCAM-1) was measured using a multiplex assay for flow cytometry.CRP-stimulated expression of ICAM-1 and E-selectin was dependent on the specific Fc?RIIa-genotype, with most pronounced induction in HUVEC with the Fc?RIIa-R/R genotype, followed by H/R and H/H. In accordance with this finding, the supernatants of stimulated HUVEC with the R/R genotype showed significantly higher levels of tPA, MCP-1, and IL-6. Our data show that CRP stimulates the expression of adhesion molecules and the release of soluble markers by HUVEC as a function of the Fc?RIIa-genotype. These findings could be relevant in the context of risk stratification in patients with cardiovascular disease.
EVALuna2:9209

Transient decrease in circulating dendritic cell precursors after acute stroke: Potential recruitment into the brain - Yilmaz, Atilla; Fuchs, Tanja; Dietel, Barbara; Altendorf, Regina; Cicha, Iwona; Stumpf, Christian; Schellinger, Peter D.; Blümcke, Ingmar; Schwab, Stefan; Daniel, Werner; Garlichs, Christoph; Kollmar, Rainer (Clinical Science, 2010)
The role of DCs (dendritic cells) as potent mediators of inflammation has not been sufficiently investigated in stroke. Therefore, in the present study, circulating mDCPs (myeloid DC precursors), pDCPs (plasmacytoid DCPs) and tDCPs (total DCPs) were analysed by flow cytometry in (i) healthy controls (n = 29), (ii) patients with ACI-S (asymptomatic cerebral infarction stenosis; n = 46), (iii) patients with TIA (transient ischaemic attack; n = 39), (iv) patients with AIS (acute ischaemic stroke; n = 73), and (v) patients with AHS (acute haemorrhagic stroke; n = 31). The NIHSS (National Institutes of Health Stroke Scale) and infarction size on a CT (computer tomography) scan were evaluated after stroke. In a patient subgroup, post-mortem immunohistochemical brain analyses were performed to detect mDCs (CD209), pDCs (CD123), T-cells (CD3) and HLA-DR. In AIS and AHS, the numbers of circulating mDCPs (P < 0.005), pDCPs (P < 0.005) and tDCPs (P < 0.001) were significantly reduced. A significant inverse correlation was found between the NIHSS and circulating DCPs (P < 0.02), as well as between hsCRP (high-sensitivity C-reactive protein) and circulating DCPs (P < 0.001). Patients with large stroke sizes on a CT scan had significantly lower numbers of mDCPs (P = 0.007), pDCPs (P = 0.05) and tDCPs (P = 0.01) than those with smaller stroke sizes. Follow-up analysis showed a significant recovery of circulating DCPs in the first few days after stroke. In the infarcted brain, a dense infiltration of mDCs co-localized with T-cells, single pDCs and high HLA-DR expression were observed. In conclusion, acute stroke leads to a decrease in circulating DCPs. Potentially, circulating DCPs are recruited from the blood into the infarcted brain and probably trigger cerebral immune reactions there. © The Authors Journal compilation © 2010 Biochemical Society.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Dendritic cell; Inflammation; Ischaemic brain injury; Leucocyte infiltration; Stroke; T-cell activation